Respostas

2014-03-10T15:41:16-03:00
A₂₀ = 2

S₅₀ = 650

a₂₀ = a₁ + (20 - 1).r ⇒ 2 = a₁ + 19.r ⇒ a₁ = 2 - 19r

S₅₀ = [(a₁ + a₅₀).50]/2 ⇒ 650 = (a₁ + a₅₀).25 ⇒ a₁ + a₅₀ = 26 ⇒ 2 - 19r + a₅₀ = 26 ⇒
                                                                                        ⇒ a₅₀ = 24 + 19r

a₅₀ = a₁ + 49r = 2 - 19r + 49r = 2 + 30r

24 + 19r = 2 + 30r ⇒ 11r = 22 ⇒ r = 2 a₁ = 2 - 19.2 = 2 - 38 = - 36
                                                        ⇒ a₅₀ = 2 + 30r = 62

P.A (- 36, - 34, - 32, -30, ..., - 2, 0, 2, 4, 6, 8, ..., 62, ...)